2017
DOI: 10.1016/j.jhealeco.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Reputational concerns with altruistic providers

Abstract: We study a model of reputational concerns when doctors differ in their degree of altruism and they can signal their altruism by their (observable) quality. When reputational concerns are high, following the introduction or enhancement of public reporting, the less altruistic (bad) doctor mimics the more altruistic (good) doctor. Otherwise, either a separating or a semi-separating equilibrium arises: the bad doctor mimics the good doctor with probability less than one. Pay-for-performance incentive schemes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Urda et al [31] pointed out that altruistic preferences not only affect decision utility functions, but also influence people’s decisions, emotions and behaviors. Olivella et al [32] studied the altruistic preference between doctors and found that when paying more attention to personal reputation, doctors with lower altruism would imitate doctors with higher a preference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urda et al [31] pointed out that altruistic preferences not only affect decision utility functions, but also influence people’s decisions, emotions and behaviors. Olivella et al [32] studied the altruistic preference between doctors and found that when paying more attention to personal reputation, doctors with lower altruism would imitate doctors with higher a preference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the DCE results showed that healthcare providers also valued the higher level of healthcare team. Except the professional nature, which determines their instinct to provide better services to residents, altruistic behavior that has been proven in the previous studies may also explain these preference choices ( 29 , 30 ). Moreover, results from previous studies have suggested FDs' role as perfect agent for their patients can be strengthened in the presence of an effective governance and operating environment ( 20 , 31 ).…”
Section: Discussionmentioning
confidence: 84%
“…Noting that min x∈P U (x, x) ≤ U (x, x), ∀x ∈ P, we have min g∈BR(s) U (g • s(x), x) ≤ U (x, x), ∀x ∈ P, ∀P ∈ P(s). (12) Note that if s • ∈ A S is a one-to-one mapping then every set P in P(s • ) is a singleton set and B R (s • ) = {s −1 • }. Thus, for all one-to-one mappings s…”
Section: Characterization Of the Stackelberg Equilibriummentioning
confidence: 99%